If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + v)(3v + 4) = 0 Reorder the terms: (9 + v)(4 + 3v) = 0 Multiply (9 + v) * (4 + 3v) (9(4 + 3v) + v(4 + 3v)) = 0 ((4 * 9 + 3v * 9) + v(4 + 3v)) = 0 ((36 + 27v) + v(4 + 3v)) = 0 (36 + 27v + (4 * v + 3v * v)) = 0 (36 + 27v + (4v + 3v2)) = 0 Combine like terms: 27v + 4v = 31v (36 + 31v + 3v2) = 0 Solving 36 + 31v + 3v2 = 0 Solving for variable 'v'. Factor a trinomial. (9 + v)(4 + 3v) = 0Subproblem 1
Set the factor '(9 + v)' equal to zero and attempt to solve: Simplifying 9 + v = 0 Solving 9 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + v = 0 + -9 Combine like terms: 9 + -9 = 0 0 + v = 0 + -9 v = 0 + -9 Combine like terms: 0 + -9 = -9 v = -9 Simplifying v = -9Subproblem 2
Set the factor '(4 + 3v)' equal to zero and attempt to solve: Simplifying 4 + 3v = 0 Solving 4 + 3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3v = 0 + -4 3v = 0 + -4 Combine like terms: 0 + -4 = -4 3v = -4 Divide each side by '3'. v = -1.333333333 Simplifying v = -1.333333333Solution
v = {-9, -1.333333333}
| 4x+3y+z=15 | | (9+v)(3v-4)=0 | | 11w=-16+7m | | 25(8x-16)+4x-4=50(6x+4)-1 | | A-5Ab=t | | 4x+6+8v=6x-6+3x | | A+5AB=t | | 4x^2-11x+9=-4x+6 | | 2(x+3)-x+4=2(x-10)+5 | | 9-6(4-3x)=24x-15 | | 3x-2-4=x | | 4p-3p+10p+2p-4p= | | 3m^2+11M+8=0 | | b-1+8b=34 | | 14+3x=28 | | 6.9=8.5-0.2x | | 9w-6w-2w=20 | | 6x+7=-47-7x | | -3x+x-8=12-2x | | x^2-5x-26=10 | | x+90+4x= | | x^2+7x+13=-5x+2 | | -3x+x-8=-12-2x | | -48-56b=-31+3b | | 2.50x-2.25=9.25 | | x^2+9x-15=-2x-3 | | 2d-d+d-d=20 | | 3x+21=10x-46 | | x^2+12x+39=4 | | 5(2x+4-2y)= | | 18g-17g+2g-3g+3g=9 | | (C+8)and(c-5)= |